MENGUKUR SIFAT ASAS UNUS TESTIS NULLUS TESTIS TERHADAP PEMBUKTIAN TINDAK PIDANA KEKERASAN SEKSUAL - Ilhami, Maulana Daffa; Afifah, Wiwik (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
There is no handling in cases of criminal acts of sexual violence or sexual crimes which is the fault of the government and can violate human rights because basically, the state is making regulations to prevent the occurrence of a crime that can harm its people. The importance of law in a country, of which is to create a comfortable scope so that people become safe in carrying out their activities. Statistically, sexual violence or sexual crimes are still targeting women, this is due to a difference in relations in which women are generally considered the lowest so victims of sexual crimes or sexual violence are still predominantly committed against women. Apart from that, there are also targets for children who still do not have enough knowledge about their bodily functions, so perpetrators of sexual crimes can persuade the child by offering objects that the victim likes or by threatening the victim. The low reporting of cases of sexual violence is also still passive because fear of the surrounding community does not help victims, but has a negative impact such as isolating or discriminating against victims so that victims become exploited by society. This can traumatize victims of sexual violence or sexual crimes. In addition to trauma being an obstacle to reporting, there was also a lack of evidence, most victims told more about the violence perpetrated against them someone so in reporting, the victim only invited a friend or someone to be a witness. this also becomes difficult considering that there is the principle of unus testis nullus testis which means that one witness is not a witness, because the testimony of a witness cannot convince a judge in passing a decision on the perpetrators of sexual violence or sexual crimes if it is not accompanied by other evidence.